Optimasi Formula Tablet Kempa Langsung Perasan Bengle (Zingiber Purpureum Roxb) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT This study was initiated by squeezing chopped fresh bengle (Zingiber purpureum Roxb). The liquid obtained was freed from amylum by filtration and the filtrate (25 ml) was dried to become powder by Aerosil (1.268 g) addition. The dried powder obtained was measured its physical properties. The exipient for dosage form was selected based on their physical properties. The optimization of formulation was done by simplex lattice design special cubic model and ten formulas was designed. The first seven formulas were used to estimate the parameter in the equation Y = B^ + B2X2 + B3X3 + B12XaX2 + B^X^ + B^X^ + B^XJXJXJ and the last three formula were used to check the validity of the equation. Those formulas contained mixture of bengle-Aerosil (200 mg), Avicel (225 mg), Starch 1500, Amprotab, and talc. The optimization of formulation was done by combining the weight of Starch 1500, Amprotab, and talc among 0-75 mg. The physical properties and Curcumin concentration in the dosage form were measured. The result indicated that all formulas were at the range of ideal physical properties (as defined in textbook) except the third formula (containing bengle 200 mg, Avicel 225 mg, and talc 75 mg). The tablets have uniformity concentration of Curcumin showed by small number of coefficient variation value. Optimization of formulation using this method produced wide area of combination mixture. The second formula (containing bengle 200 mg, Avicel 225 mg, and Amprotab 75 mg) was considered the best formula because it performed the high hardness (7.2 kg) but the disintegration time was lowest (41.2 s).